Raakpunte in die ontwikkeling van ekumene in die wêreld met ekumeniese ontwikkelinge in die gereformeerde kerke in Suid-Afrika (1990-2020) - van der Merwe, Rudolph (Stellenbosch Theological Journal, 2021)
Points of communality in the development of ecumenism worldwide with reformed churches in South Africa (1990-2020) This historic-critical study analyses the development of ecumenism from 1990 to 2020 within the traditional Afrikaans speaking reformed churches in South Africa. The study attempts to determine whether the so-called change or shift in ecumenism within reformed churches and ecumenical bodies worldwide, influenced the theology and practice of ecumenism in Afrikaans-speaking churches in South Africa (1990 to 2020). Afrikaans-speaking reformed churches not only face political and social challenges in South Africa, but also face other major challenges brought about by a postmodern society and theological developments from 1990 to 2020. The development of ecumenism in reformed churches in the world, as described by Plaatjies-Van Huffel (2011:1-11) consists of a shift from conciliar ecumenism to transformative receptive ecumenism. In the past 30 years conciliar ecumenism took its stance in absolute certainties derived from a specific viewpoint on Scripture. Conciliar ecumenism partially failed because some reformed churches excluded other reformed churches from church unity, based on a particular interpretation of Scripture. These exclusions were claimed to be based upon the “authority” derived from Scripture. This ecumenical practice did not lead to significant church unity. The transformative receptive ecumenism, on the other hand, tends to reach out to the marginalised people of God, and not only try to transform the unrighteousness in the lives of people, but also tends to learn from and accommodate the needy in the understanding of ecumenism. If the developments in worldwide ecumenism influenced ecumenical thought among reformed Afrikaans-speaking churches, the question arises: to what extent was transformative receptive ecumenism able to contribute to a better understanding of ecumenism and church unity - especially in the development of an African transformative receptive ecumenism. Also, if a shift in ecumenical practise took place, does that mean that the conciliar ecumenism of the past was of minimal importance? Is a new understanding of ecumenism (as in transformative receptive ecumenism) the alpha and omega of ecumenism in theory and practice? Shouldn't transformative receptive ecumenism be further discussed by all churches in South Africa and the world to bring forth an ecumenical model that suits the South African situation as part of worldwide ecumenism? This chapter attempts to understand recent developments and issues within the reformed ecumenical societies and agencies in the world, after which the Afrikaans-speaking historic-reformed churches will be viewed in terms of the understanding of their calling to ecumenism. The developments and issues in the reformed world will be compared with the latest developments and issues within the Afrikaans-speaking reformed churches. A conclusion based on a comparison between ecumenism in the world and in South Africa will be drawn before some remarks on the future of ecumenical understanding concludes this study.